2017
DOI: 10.1128/jcm.00318-17
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Clinical Evaluation of the Luminex Aries Flu A/B & RSV Assay for Pediatric and Adult Respiratory Tract Specimens

Abstract: Influenza A and B viruses and respiratory syncytial virus (RSV) are three common viruses implicated in seasonal respiratory tract infections and are a major cause of morbidity and mortality in adults and children worldwide. In recent years, an increasing number of commercial molecular tests have become available to diagnose respiratory viral infections. The Luminex Aries Flu A/B & RSV assay is a fully automated sample-to-answer molecular diagnostic assay for the detection of influenza A, influenza B, and RSV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Our study showed similar sensitivities and specificities for FluA (98.6% and 99.3%, respectively), FluB (97.9% and 99.4%, respectively), and RSV (99.1% and 98.4%, respectively) by Xpert. A multicenter clinical evaluation of the Aries system reported 95.8%, 93.8%, and 97.1% PPA for FluA, FluB, and RSV, respectively, a 98.4% NPA for FluA and RSV, and a 99.4% NPA for FluB (20). We report a higher specificity for all three targets with Aries and comparable sensitivities in our study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our study showed similar sensitivities and specificities for FluA (98.6% and 99.3%, respectively), FluB (97.9% and 99.4%, respectively), and RSV (99.1% and 98.4%, respectively) by Xpert. A multicenter clinical evaluation of the Aries system reported 95.8%, 93.8%, and 97.1% PPA for FluA, FluB, and RSV, respectively, a 98.4% NPA for FluA and RSV, and a 99.4% NPA for FluB (20). We report a higher specificity for all three targets with Aries and comparable sensitivities in our study.…”
Section: Discussionsupporting
confidence: 77%
“…Traditional reverse transcription-PCRs (RT-PCRs) require nucleic acid extraction prior to the amplification process, a low-to moderate-complexity (MC) instrument, trained personnel to perform both extraction and PCR, and manual interpretation of results, necessitating a TAT of approximately 3 to 4 h. The recently introduced automated sample-to-answer (STA) NAAT systems have improved the ease of use and provide moderate to highly accurate test results with a faster TAT. At present, a number of STA FluA/B and RSV molecular assays are approved by the Food and Drug Administration (FDA) and available for clinical use: GeneXpert Xpress Flu/RSV (Xpert; Cepheid, Sunnyvale, CA) (15,16), Diasorin Simplexa Flu A/B & RSV (Simplexa; Diasorin Molecular, Cypress, CA) (17), Alere (Abbott Rapid Diagnostics, IL) (18,19), Aries Flu A/B & RSV (Aries; Luminex Corporation, Austin, TX) (20), Cobas influenza A/B & RSV (Liat; Roche Diagnostics, Indianapolis, IN) (21), BioFire FilmArray respiratory panel (RP; BioFire Diagnostics, Salt Lake City, UT), and Panther Fusion Flu A/B/RSV (Fusion; Hologic Inc., San Diego, CA), among others (https:// www.cdc.gov/flu/professionals/diagnosis/table-nucleic-acid-detection.html). Of these STA assays, Alere, Liat, and Xpert offer Clinical Laboratory Improvement Amendments (CLIA)-waived (CW) assays suitable for point-of-care (POC) testing by nonlaboratory personnel to provide test results within 15 to 30 min in outpatient settings (21,22).…”
mentioning
confidence: 99%
“…Technologists performing the Aries BA testing were blinded to the results of the FilmArray RP testing. Aries BA testing was performed on 200 l of each residual sample according to the manufacturer's instructions and as previously described (11). Residual samples were stored at Ϫ80°C for discordant testing when applicable.…”
Section: Methodsmentioning
confidence: 99%
“…Among innumerable examples during the 10 years are national and international leadership in responding to the novel H1N1 influenza virus pandemic in 2009 18 ; demonstrating how in-system consolidation of anatomic pathology services can help drive subspecialization to support high-acuity patient care 14 ; and improvement in diagnostics for respiratory virus infections. 19 The consistent year-to-year effort to advance the delivery of health care is an essential element of being an effective insystem laboratory. Patient care is also served through leadership and volunteerism provided by pathology medical and managerial personnel at all levels of the institution and throughout its extensive geography.…”
Section: Value-added Outcomesmentioning
confidence: 99%